If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -148 = 3x + 566 Reorder the terms: -148 + 4x = 3x + 566 Reorder the terms: -148 + 4x = 566 + 3x Solving -148 + 4x = 566 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -148 + 4x + -3x = 566 + 3x + -3x Combine like terms: 4x + -3x = 1x -148 + 1x = 566 + 3x + -3x Combine like terms: 3x + -3x = 0 -148 + 1x = 566 + 0 -148 + 1x = 566 Add '148' to each side of the equation. -148 + 148 + 1x = 566 + 148 Combine like terms: -148 + 148 = 0 0 + 1x = 566 + 148 1x = 566 + 148 Combine like terms: 566 + 148 = 714 1x = 714 Divide each side by '1'. x = 714 Simplifying x = 714
| 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 | | 12+3(z-4)=-5z+5 | | -3(x+12)=16-x | | -6(n+3)+21=-3n-6 | | -2(2x+5)= | | 1x+2y+3z=18 | | (2x+13)=-81 | | 4(2x-6)= |